MODEL PEMBELAJARAN PAI BERBASIS PROYEK UNTUK MENUMBUHKAN KREATIVITAS DAN KEMANDIRIAN SISWA SD - Afrianto, Gatot; Mega Sukma; Rosynanda Nur Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of Islamic Religious Education (PAI) at the elementary school level tends to remain oriented toward conventional methods such as lecturing and memorization. This pattern limits students’ opportunities to engage actively, take initiative, and develop creativity and independence in the learning process. In fact, the core purpose of PAI is not merely the transmission of religious knowledge but also the cultivation of character values such as responsibility, independence, and creativity. This study seeks to examine the application of a project-based learning model in PAI as an alternative strategy to foster creativity and independence among elementary school students. A descriptive qualitative approach was employed, involving fifth-grade students, PAI teachers, and school principals as primary and supporting informants. Data were collected through observation, in-depth interviews, and document analysis. The findings indicate that the implementation of the project-based learning model had a positive impact on enhancing students’ creativity and independence. Their creativity was evident when they engaged in activities such as creating dakwah posters and independently designing worship schedules, where they were given the freedom to plan and express their ideas. Independence was reflected in students’ ability to manage their time, complete tasks responsibly, and reduce reliance on teachers. Moreover, this approach contributed to increasing learning motivation, building self-confidence, and providing more meaningful learning experiences. The project-based PAI learning model can thus be regarded as an educational innovation at the elementary level, as it not only supports academic achievement but also reinforces character development in alignment with the principles of the Merdeka Curriculum.